Banana leathers as influenced by polysaccharide matrix and probiotic bacteria - Niro, Carolina Madazio; Medeiros, Jackson Andson de [UNESP]; Bresolin, Joana Dias; Dionísio, Ana Paula; Salgaço, Mateus Kawata [UNESP]; Sivieri, Katia [UNESP]; Azeredo, Henriette M.C. (Elsevier, 2022)
Concerns abouth diet-health relationships have led many people to include healthier snacks in their diets, including those with functional (including probiotic) properties. This study was focused on development of probiotic-loaded banana leathers. Two probiotic bacteria (the spore-forming Bacillus coagulans and the conventional non-spore-forming Lactobacillus acidophilus) and two polymeric matrices (digestible cassava starch and non-digestible bacterial cellulose - BC) have been used. The presence of probiotic bacteria (mainly L. acidophilus) reduced the tensile strength, elastic modulus and shear force of the leathers, while the BC-based leathers were stronger, stiffer and more resistant to shear stress than the starch-based ones. While a high probiotic viability was kept on fruit leathers loaded with B. coagulans during drying and room-temperature storage, those loaded with L. acidophilus suffered high viability losses upon drying, which was ascribed to osmotic stress. The nature of the biopolymeric matrix has not significantly influence the bacterial viability losses along processing and storage, or the final viable cell count released into the intestine (as assessed using an INFOGEST static in vitro simulated digestion model). The banana leathers loaded with B. coagulans were well accepted, irrespectively of being produced from BC or starch, although some negative comments on the texture and flavor of the BC-based ones have been more frequent than with the starch-based ones.
Keywords: Fruit-based snacks; Polysaccharides; Probiotic food; Static gastrointestinal model; Tensile properties